Digital Transformation and Multilingual Language Education in Makassar's Higher Education: A Mixed-Methods Study of Students and Faculty - Muhammad Nurahmad; Zulkhaeriyah Zulkhaeriyah; Nuraziza Aliah; Nurasia Natsir (AL-ISHLAH: Jurnal Pendidikan, 2025)
In Indonesia’s multilingual higher education landscape, especially in Eastern regions like Makassar, institutions face growing challenges in developing students' academic literacy in both Indonesian and English amid rapid digital transformation. This study investigates how digital tools, pedagogical practices, and cultural factors intersect in shaping language learning outcomes. Using a sequential explanatory mixed-methods design, the study surveyed 200 students and 50 faculty members across five universities in Makassar, followed by interviews, focus groups, and classroom observations conducted between August 2023 and March 2024. Quantitative data included self-assessed language proficiency, digital literacy, and learning motivation. Qualitative data provided contextual insights into classroom practices and institutional dynamics. Quantitative analysis revealed major gaps in productive English skills—73% of students reported difficulties in speaking—and substantial challenges in Indonesian academic writing. Faculty quality (β = 0.79, p .001) and student motivation (β = 0.72, p .01) were the strongest predictors of success. Qualitative findings emphasized the role of translanguaging, culturally responsive teaching, and the digital divide in shaping learning experiences. A hybrid learning model (40% online, 60% face-to-face) integrating translanguaging strategies and local cultural practices emerged as a promising approach. The study recommends faculty development in digital pedagogy and inclusive curriculum design. Strengthening multilingual education in resource-constrained contexts requires context-specific innovations that bridge global competencies with local identities through culturally grounded digital transformation.